Identifying and evaluating supply chain activities: a case study on Auto Equipment Limited - Hoque, A.H.M. Rakibul (BARC University, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.